Influence of pre-analytical conditions on plasma ribavirin concentrations - Gandia, Peggy; Trancart, Stéphanie; Nicot, Florence; Barange, Karl; Alric, Laurent; Izopet, Jacques; Séraissol, Patrick; Lavit, Michel; Houin, Georges (Arzneimittelforschung, 2010)
Ribavirin (CAS 66510-90-5) associated to peginterferon (CAS 99210-65-8) is the current Standard treatment for chronic hepatitis C. Exposure to ribavirin influences the virological response and anemia. Therefore monitoring plasma concentration of ribavirin is a useful tool for individualizing ribavirin dosing regimens. Ribavirin is a substrate of several nucleoside transporters that play a role in its distribution in erythrocytes. After blood sampling, it is essential to limit this mechanism. The aim of this study was to evaluate the influence of temperature and time on ribavirin plasma concentrations.Two blood samples, collected in EDTA tubes, were taken at the same time from 23 patients. One sample was conserved on ice whereas the second one was kept at room temperature during transport to the laboratory. Upon receipt at the laboratory and at different times post-reception (from 1 to 3 h), 1.5 mL of blood from each sample was centrifuged to obtain plasma that was then stored at −20 °C until assay. Samples were maintained in the same conditions as during transport for the 3 h. Plasma ribavirin was analysed using an HPLC-UV system.The results showed that mean loss of ribavirin concentration, for samples kept on ice as well as at room temperature, was less than 3%, 9% and 13% after 1, 2 and 3 h, respectively. These results suggest that blood samples for ribavirin analysis can be sent at room temperature within a period of 2 h between sampling and centrifugation.
Keywords: Antiviral drugs; CAS 66510-90-5; High-performance liquid chromatography; Ribavirin; Therapeutic drug monitoring